Rural non-farm employment in Uttar Pradesh, India: drivers and impact - Shreya Kapoor; Anjani Kumar; Sunil Saroj (Agricultural Economics Research Review, 2023)
The agriculture sector is facing disguised unemployment and the workforce is migrating from the farm sector to the non-farm sector. This study examines rural non-farm employment patterns in Uttar Pradesh, India, to identify the drivers of household employment choices and the impact of increased income levels on poverty. The shift from the agricultural sector to the non-farm sector—across all expenditure and landholding classes—is drastic. If non-farm employment increases, household income rises and rural poverty falls. Promoting crop diversification—and providing extensive infrastructure, financial, and technological support—could help localized micro-enterprises engage in post-harvest activities.